Comparison of immunodiffusion and enzyme linked immunosorbent assay in the detection of abnormal antibodies in pigeon breeder's disease. Issue 6 (June 1992) - Simpson, C; Shirodaria, P V; Evans, J P; Simpson, D I; Stanford, C F
Abstract : AIMS: To compare the sensitivity of two methods for the detection of serum antibodies to pigeon faecal antigens in patients with pigeon breeder's disease. METHODS: Serum samples stored at -20 degrees C from 50 patients with pigeon breeder's disease, 50 control samples from patients with other respiratory diseases, and 50 healthy blood donors were examined for the precipitating antibodies and IgG antibodies to antigens present in extract of pigeon droppings by immunodiffusion and enzyme linked immunosorbent assay (ELISA), respectively. RESULTS: Both antigen preparations of pigeon dropping extract were equally effective. A positive immunodiffusion reaction gave one or more precipitin lines and these antibodies were detected only in undiluted sera from 80% of the patients with pigeon breeder's disease. In the ELISA the sera were tested at a starting dilution of 1 in 100 because positive reactions were observed with sera from healthy blood donors at lower dilutions. All sera which gave optical density readings above 3 SD of the control value were considered to have IgG antibodies. These antibodies were detected in sera from all the patients with pigeon breeder's disease. The antibody titres were much higher in those patients who had precipitating antibodies (range 800-51, 200) than those without (range 100-800). The antibodies were not detected in the sera of patients with respiratory diseases or healthy blood donors by either method. CONCLUSIONS: Antibodies to pigeon dropping antigens were detected by immunodiffusion and ELISA in sera from patients with pigeon breeder's disease but not in control sera. ELISA was a more sensitive method for detecting antibodies and therefore seems to have considerable potential as a routine technique in the serological diagnosis of pigeon breeder's disease.